Evaluation of the physical and mechanical properties of concrete blocks prepared with partial replacement of the aggregate by sand and silica powder (Gaceta Técnica, 2024)
The aim of this research is to evaluate the influence of silica dust and sand in the concrete mixture for the production of blocks. 14 blocks were manufactured with 20% silica sand replacing the natural aggregate and adding 15% silica powder, in addition to 14 blocks with a master mix; Pre-established tests in the COVENIN 42-82 standard were carried out on each sample at 28 and 90 days to evaluate its physical and mechanical properties. One of the physical properties evaluated was dimensional stability; the results were similar for both samples, since they were made under the same conditions and the silica did not affect their dimensions. The other physical property is the absorption capacity of the blocks, which gave similar results at 28 days between the two samples and at 90 days, registering an increase in the standard sample with an average of 8,54% and a decrease in silica. with an average of 7.05%, all complying with the range established by the Venezuelan standard COVENIN 42-82. The mechanical property evaluated was compressive strength, after 28 days the standard sample did not reach the minimum accepted resistance while the sample with silica did reach said standard, and after 90 days the standard sample maintained the registered resistance while the sample with silica increased. your values.
Keywords: concrete; reinforced concrete; concrete blocks; silica sand; silica powder